Proceedings of the 2018 Designing Interactive Systems Conference 2018
DOI: 10.1145/3196709.3196804
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Hygge as a Desirable Design Vision for the Sustainable Smart Home

Abstract: In this paper, we present an exploratory study of hygge as a low-energy design vision for the smart home. Hygge is a Danish concept that embodies aesthetic experiences related to conviviality, often shaped by orchestrating atmospheres through low-level lighting. To explore this vision, we probe two Australian households that already live with smart home lighting technology. We report on household reflections of embedding hygge into everyday life. We conclude by outlining future directions for exploring desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Using the cards, we learned how participants understood, experienced, and pursued comfort. In line with other social research, we found that comfort was a flexible and multifaceted idea which could not be reduced to thermal considerations alone (Jensen et al, 2018; Vannini & Taggart, 2013). For example, several participants across the three field sites explained that they associated “ Uncomfortable ” with summer, because of the high temperatures and because the heat represented what Stucco resident Bruce called an “unmodifiable discomfort” that could not be resolved without resorting to some form of mechanical air conditioning.…”
Section: Understanding Energy Generation and Everyday Practicessupporting
confidence: 91%
“…Using the cards, we learned how participants understood, experienced, and pursued comfort. In line with other social research, we found that comfort was a flexible and multifaceted idea which could not be reduced to thermal considerations alone (Jensen et al, 2018; Vannini & Taggart, 2013). For example, several participants across the three field sites explained that they associated “ Uncomfortable ” with summer, because of the high temperatures and because the heat represented what Stucco resident Bruce called an “unmodifiable discomfort” that could not be resolved without resorting to some form of mechanical air conditioning.…”
Section: Understanding Energy Generation and Everyday Practicessupporting
confidence: 91%
“…The opportunities for re-envisioning pleasance are endless, and could involve or exclude smart home technologies. One method is to imagine and design desirable ways of life into devices that use less energy, as we have begun to do elsewhere with colleagues (Jensen et al 2018a(Jensen et al , 2018b. HCI and related disciplines provide much inspiration for this.…”
Section: Discussion: Implications For Work On Sustainability In Hcimentioning
confidence: 99%
“…While hygge also implicitly requires energy demand, it does not rely heavily on technology. In a related study conducted with some of the authors of this paper, hygge provides inspiration for HCI scholars interested in reframing what the desirable and low-energy smart home might look like, through the example of lighting (Jensen et al, 2018b).…”
Section: Automated Lighting: Lower Energy Aesthetic Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Restorative spaces have begun to emerge in office settings in recent years (Pochepan, 2018) and may include areas designated for specific activities such as sleep pods, meditation spaces, yoga rooms, and indoor and outdoor "rooms" where employees can immerse themselves in nature. Home designers may also draw increasingly on the Danish concept of hygge (Jensen, Strengers, Raptis, Nicholls, Kjeldskov, & Skov, 2018), the idea of designing homes and the activities that occur in them to promote a feeling of comfort, cosiness and connection. A part of this design may now include the separation of work and private spaces within the home.…”
Section: Policy Makers and Designersmentioning
confidence: 99%